3T MR imaging evaluation of perianal fistulas: an initial experience in Nepal - Gurung, Ghanshyam (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Fistula–in–ano is an abnormal perianal tract that connects anal canal to the perianal skin. Improper visualization of primary fistulous tract and the associated abscesses or secondary tracts a r e the causes of recurrence. Earlier imaging modalities like conventional fistulography, endosonography and CT scan have had limited role. Even without endorectal coils, 3T MRI has multi-planar imaging capability and excellent soft tissue differentiation to show perianal anatomy, primary and secondary tracts with associated abscesses in relation to sphincter complex. It provides excellent road map to surgeons for preoperative evaluation. The objective of the study was to evaluate the role of 3T MR in imaging of perianal fistulas.Methods: A retrospective study was done among 32 patients who were referred for MR fistulogram for suspected perianal fistula at Jeebanta Advanced Kathmandu Imaging, Durbar Marg, Kathmandu, Nepal. All images and findings were obtained and recorded with the help of Philips Ingenia 3T digital broadband MR scanner. Imaging was performed in oblique coronal and oblique axial plane. MR images were studied and grading system was applied according to the St James’s University Hospital Classification. The data were entered in a performa and was analyzed using IBM SPSS V21.Results: Male to female ratio was 7:1. According to St. James University Hospital MR Imaging classification of perianal fistulas, most of the patients (25%) had Grade 4 followed by (12.5% each) Grade 0, Grade 1 and Grade 2 and (6.3% each) Grade 3 and Grade 5 fistulas. Mean age was 37.28 years (Std. deviation 11.9). Common internal opening in axial image was found at 5 0’ clock positions (31.3%). Mean length of the fistulous tract was 3.9 cm (Std. deviation 2.3).Conclusion: Perianal fistulas are more common in males and Grade 4 fistulas are the commonest. MRI is well-tolerated, painless and non-invasive technique and has multiplanar capabilities with excellent tissue differentiation of pelvic muscle along with sphincter complex.